Estágio supervisionado e prática docente: Sentidos das produções discursivas da ANPEd, BDTD e EPENN. Supervised internship and teachers practice: Meanings of the discursive productions of ANPEd, BDTD and EPENN - Melo, Maria Julia C. de (Revista Eletrônica de Educação, 2014)
This article aims to analyze the meanings assigned to supervised internship and teachers practice on the discursive productions of ANPEd, UFPE’s BDTD and EPENN, Brazil. These meanings are understood as having a dynamic character, always being historically resignified and occupying epistemic and political disputes’ place. Therefore, this article starts with the discussion on the historically established relationship between theory and practice in teachers’ education; it also addresses the dialogue on the challenges of internship; moves forward to the debate about teachers practice, in addition to the publications themselves that were at the same time theoretical and analysis references. Methodologically, this article embraced qualitative approach, analyzing scientific publications from the French perspective of Discourse Analysis. Thus, the published papers bring the internship as an opportunity to establish praxis and dialogue between the several curriculum components. In addition, the internship linked to the reflection’s enunciation presents itself as a place of resignification of teachers practice. The papers also establish links between theory of reflective practice and Marxist slant theory of praxis. Nevertheless, the analyzed productions on internship and teaching practice make use of both conceptions on the attempt to establish the relationship between theory and practice. Este artigo objetiva analisar os sentidos atribuídos ao estágio supervisionado e à prática docente nas produções discursivas da ANPEd, BDTD da UFPE, e EPENN, Brasil. Esses sentidos são compreendidos como tendo um caráter dinâmico, sempre ressignificados historicamente e ocupando o lugar de disputas epistêmicas e políticas. Assim, o artigo inicia com a discussão sobre a relação teoria e prática historicamente construída na formação de professores; investe ainda no diálogo sobre os desafios do estágio; discorrendo com o debate a respeito da prática docente; além das próprias publicações que foram ao mesmo tempo referência teórica e análise. Como metodologia o artigo se filia à abordagem qualitativa, analisando as publicações científicas a partir da Análise do Discurso na perspectiva francesa. Dessa forma, os trabalhos publicados trazem o estágio como possibilidade de construção da práxis e de diálogo entre os diversos componentes curriculares. Além disso, o estágio articulado ao enunciado da reflexão se apresenta como lugar de ressignificação da prática docente. Identifica-se que os trabalhos ainda estabelecem vínculos entre a teoria da prática reflexiva e a teoria da práxis de cunho mais marxista. Sem embargo, as produções analisadas tanto de estágio quanto de prática docente se utilizam das duas concepções na tentativa de estabelecer a relação teoria e prática.